Adapting cognitive therapy for depression : managing complexity and comorbidity - Whisman, Mark A. (Guilford Press, 2008)
Presents a unified set of clinical guidelines for conceptualizing, assessing, and treating challenging presentations of depression. This book also offers knowledge and tools for delivering competent care to specific populations of depressed patients: ethnic minorities; lesbian, gay, and bisexual people; adolescents; and older adults.